Pathogenesis of (smoking-related) non-communicable diseases—Evidence for a common underlying pathophysiological pattern - Kopp, Wolfgang (Frontiers in Physiology, 2022)
Noncommunicable diseases, like diabetes, cardiovascular diseases, cancer, stroke, chronic obstructive pulmonary disease, osteoporosis, arthritis, Alzheimer’s disease and other more are a leading cause of death in almost all countries. Lifestyle factors, especially poor diet and tobacco consumption, are considered to be the most important influencing factors in the development of these diseases. The Western diet has been shown to cause a significant distortion of normal physiology, characterized by dysregulation of the sympathetic nervous system, renin-angiotensin system, and immune system, as well as disruption of physiological insulin and oxidant/antioxidant homeostasis, all of which play critical roles in the development of these diseases. This paper addresses the question of whether the development of smoking-related noncommunicative diseases follows the same pathophysiological pattern. The evidence presented shows for the first time that exposure to cigarette smoke and/or nicotine causes the same complex dysregulation of physiology as described above, it further shows that the factors involved are strongly interrelated, and that all of these factors play a key role in the development of a broad spectrum of smoking-related diseases. Since not all smokers develop one or more of these diseases, it is proposed that this disruption of normal physiological balance represents a kind of pathogenetic “basic toolkit" for the potential development of a range of noncommunicative diseases, and that the decision of whether and what disease will develop in an individual is determined by other, individual factors ("determinants"), such as the genome, epigenome, exposome, microbiome, and others. The common pathophysiological pattern underlying these diseases may provide an explanation for the often poorly understood links between noncommunicable diseases and disease comorbidities. The proposed pathophysiological process offers new insights into the development of noncommunicable diseases and may influence the direction of future research in both prevention and therapy.